The Role of Marketing Tools in the Improvement of Consumers Financial Literacy - Paramonovs, Sergejs; Ijevleva, Ksenija (Economics and Business, 2015)
The aim of the paper is to explore the contribution of different types of marketing communication in consumer financial literacy formation from a three component perspective. As a method a survey among the target audience of home loans was used. The authors have focused on consumer financial knowledge, financial behaviour and financial attitude that constitute financial literacy in home loan market. As a result of empirical analysis the authors have found that the biggest contribution to formation of consumers financial literacy (within all three components) have educational web sites of government authorities, official web sites of banks, consultations with bank specialists, school curriculum subjects and opinions of friends, relatives and acquaintances.